Tongging Leisure Park with Neo-Vernacular Architecture Approach - Muhammad Fathur Rahman; Ginting, Nurlisa (Jurnal Koridor, 2020)
Tourism in Indonesia is one of the economic and welfare generators for the local community as well as improving the quality of life of tourists through various activities such as recreation, resting, and getting new knowledge. The Indonesian government through the Ministry of Tourism has chosen ten priority destinations that are rich in natural and cultural products which are expected to bring millions of tourists every year, one of them is Lake Toba in North Sumatra. A village near Lake Toba, namely Tongging Village is still not optimized as a tourist destination, so to attract tourists and support a variety of vacation needs, a leisure park is needed. In designing leisure parks using the Neo Vernacular Architecture approach that is suitable for the design location, because this architectural style is very concerned about natural and cultural elements in the area.